Perbandingan Metode Simple Additive Weigthing (SAW) dan Analytic Hierarchhy Process (AHP) dalam Pemilihan Lapangan Badminton Terbaik di Kota Kupang - Akeld Gamaliel Denil; Yohanis Malelak (Jurnal Manajemen Informatika & Teknologi, 2025)
The court is a badminton game area that is rectangular in shape and has a net in the middle, the increasing number of new badminton courts or what is often called gor shows that badminton is now popular among the community. This research aims to help the community in determining the choice of badminton courts based on predetermined criteria. In this study, two methods were used to make a comparison by applying the Simple Additive Weighting (SAW) and Analytical Heiarchy Process (AHP) methods. Data collection is carried out by means of observation and direct interviews with field managers, the data obtained will be implemented in a web-free Decision Support System (SPK) with the SAW and AHP methods to produce the best alternative where this method seeks the weighted sum of the best peformance ratting on each alternative on all criteria. The results of this research are in the form of a website-based system where the system can provide recommendations that can help badminton court users in choosing the appropriate badminton court.